Can goal-free problems be used to support students in solving goal-specific problems in the secondary mathematics classroom? - Wilson, J (2019)
This research project explores the extent to which goal-free problems can be used to support Year 10 students in solving goal-specific problems in the domain of circle theorems. The study compares the performance of an intervention group working on goal-free problems (n = 51) with a control group (n = 46) on a variety of goal-specific problems at the end of a sequence of ten lessons. Issues within the affective domain, such as student confidence and enjoyment of lessons, are also compared through the use of questionnaires.